Speaking anxiety among single-gender and co-educational schools students in an online learning context - Zulkiflee, Mohamad Fakhrul Aiman; Nimehchisalem, Vahid (Scientific Research Publishing, 2022)
Speaking anxiety is the fear of utilizing the language orally and it is believed to be affected by gender as distractions by counterpart gender in co-educational schools could trigger anxiety in speaking English. Moreover, due to the COVID-19 Pandemic, educational institutes have shifted to online learning which could also contribute to anxiety. Many studies have been carried out on speaking anxiety among language learners. However, to the best of our knowledge, speaking anxiety among students in single-gender and co-educational schools in an online learning context has not been explored. Therefore, this study aims to investigate the students’ speaking anxiety in three different gender-based types of schools. We adopted a mixed-method research design. The participants were 180 students for surveys and 12 students for interviews. The instruments used were the English as a Second Language Speaking Anxiety Scale (ESLSAS) adapted from Hwa and Peck (2017) which were administered through Google Forms and virtual semi-structured interviews conducted via online meeting platforms. The surveys were analyzed by employing descriptive and inferential analysis whereas the interviews were analyzed by employing content analysis. The findings revealed that the majority of the students experienced low speaking anxiety levels, female students experienced higher speaking anxiety levels than their counterpart gender, and there was a statistically significant difference between the students’ speaking anxiety mean scores in single-gender and co-educational schools. Additionally, within the context of the co-educational schools, female students’ speaking anxiety was significantly higher. The results of the analysis of the interviews indicated the sources of speaking anxiety and coping strategies employed by the students. This study provides pedagogical implications to English language educators.